Камень погибели: [роман] / Анонимус - Анонимус (ЛитРес: Детектив, 2022)
Экземпляры: Ермолаевская с/б (20240209) / Инвентарный номер: 47983 / Цена: / Авт.знак: А 69 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44